2004
DOI: 10.1097/00002371-200411000-00148
|View full text |Cite
|
Sign up to set email alerts
|

His-tag ELISA for the Detection of Humoral Tumor-Specific Immunity

Abstract: Background: The application of high throughput molecular techniques such as SEREX are resulting in the identification of a multitude of tumor associated antigens. As newly identified antigens are incorporated into a variety of clinical trials, standardization of immunologic monitoring methods becomes increasingly important. We questioned whether mammalian cell expression of a histadine-linked human protein could be used to produce antigen suitable for detecting tumorspecific humoral immunity and whether such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…(15) For murine serum samples, the same protocol was used except for the following substitutions: purified mouse recombinant IGFBP-2 protein (Sigma) and anti-mouse IgG/HRP conjugate (Zymed Laboratories). IGFBP-2 antibody immunity detected by ELISA was verified using Western blot analysis.…”
Section: Methodsmentioning
confidence: 99%
“…(15) For murine serum samples, the same protocol was used except for the following substitutions: purified mouse recombinant IGFBP-2 protein (Sigma) and anti-mouse IgG/HRP conjugate (Zymed Laboratories). IGFBP-2 antibody immunity detected by ELISA was verified using Western blot analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Goodell et al [43] demonstrated by specifically designed his-tagged capture ELISA (based on lysate from genetically engineered Chinese hamster ovary cells) the presence of AAbs to IGFBP-2 in the sera of 4/80 (5%) breast carcinoma patients, 32/80 (40%) colorectal carcinoma patients and 2/200 (1%) healthy controls. These corresponded to a significant difference between all carcinoma patients and healthy controls ( P = .008), between breast carcinoma patients and healthy controls ( P = .032), and between colorectal carcinoma patients and healthy controls ( P < .001) [43]. The authors concluded that the AAbs to IGFBP-2 assayed by capture ELISA can discriminate between cancer patients and controls [43].…”
Section: Autoantibodies To Insulin-like Growth Factor Binding Promentioning
confidence: 99%
“…These corresponded to a significant difference between all carcinoma patients and healthy controls ( P = .008), between breast carcinoma patients and healthy controls ( P = .032), and between colorectal carcinoma patients and healthy controls ( P < .001) [43]. The authors concluded that the AAbs to IGFBP-2 assayed by capture ELISA can discriminate between cancer patients and controls [43]. It seems, however, that AAbs to IGFBP-2 have little value for screening and early diagnosis of breast carcinoma when examined alone.…”
Section: Autoantibodies To Insulin-like Growth Factor Binding Promentioning
confidence: 99%